Adventurer in ranks of the secret services? To the biography of Pyotr Vasilyevich Glinko– Appin - D. I. Petin (Омский научный вестник: Серия "Общество. История. Современность")
The article deals with the problem of embedding foreigners in the early Soviet society in the conditions of the end of the Civil War in Siberia. For this purpose, on the basis of the anthropological approach, theories of social adaptation and social identity, the biography of the representative of the Czech intelligentsia Pyotr Vasilyevich Glinko–Appin is analyzed. The final stage of his life was associated with work in the special services of anti-Bolshevik and pro-Soviet authorities, being in custody, participating in the Soviet underground, and working as a civil engineer. The basis for the study is a complex of unpublished forensic and investigative materials that are part of the archival criminal case against the hero of the story. In conclusion, it is emphasized that a foreign officer with an anti-Bolshevik past could not count on successful social adaptation in the conditions of Soviet Russia.